Socioeconomic Correlates of Eating Disorder Symptoms in an Australian Population-Based Sample. - Brittany Mulders-Jones; Deborah Mitchison; Federico Girosi; Phillipa Hay (PLoS ONE)
Background Recent research has challenged the stereotype that eating disorders are largely limited to young, White, upper-class females. This study investigated the association between indicators of socioeconomic status and eating disorder features. Methods and findings Data were merged from cross-sectional general population surveys of adults in South Australia in 2008 (n = 3034) and 2009 (n = 3007) to give a total sample of 6041 participants. Multivariate logistic regressions were employed to test associations between indicators of socioeconomic status (household income, educational level, employment status, indigenous status and urbanicity) and current eating disorder features (objective binge eating, subjective binge eating, purging, strict dieting and overvaluation of weight/shape). Eating disorder features occurred at similar rates across all levels of income, education, indigenous status, and urbanicity (p > 0.05). However, compared to working full-time, not working due to disability was associated with an increased risk of objective binge eating (odds ratio (OR) = 2.30, p < 0.01) and purging (OR = 4.13, p < 0.05), engagement in home-duties with an increased risk of overvaluation of weight/shape (OR = 1.39, p < 0.05), and unemployment with an increased risk of objective binge eating (OR = 2.02, p < 0.05) and subjective binge eating (OR = 2.80, p < 0.05). Furthermore, participants with a trade or certificate qualification were at a significantly increased risk of reporting strict dieting compared to participants without a tertiary qualification (OR = 1.58, p <0.01). Limitations included the small numbers of indigenous participants (n = 115) and participants who reported purging (n = 54), exclusion of excessive exercise (which is associated with eating disorders, particularly in males), and the conduct of interviews by laypersons. Conclusions Overall, symptoms of eating disorders are distributed equally across levels of socioeconomic status. This study highlights the need for universal access to specialised services, to train healthcare workers in the detection and diagnosis of eating disorders in diverse subgroups, and to combat barriers to help-seeking experienced by people who do not conform to the demographic stereotype of an eating disorder. The increased prevalence of various eating disorder features in those who are not working could be addressed by providing support to help sufferers join the workforce, or engage in meaningful social or community activities to improve resilience against the development of eating disorders.